Urban Treeof Itapira–SP: perspectives for environmental education and its influence on thermal comfort - Martelli, Anderson; Santos Jr., Arnaldo Rodrigues dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The growth and urbanization of cities has prompted serious damage to the environmental condition as well as considerable economic, social and quality of life losses. The temperature rise is a climate change favored by the built environment due to differences between the thermal characteristics of building materials and vegetation differences. The aim of this study was to analyze the differences in temperature and relative humidity at three sites of central Itapira, SP, with similar features area, highlighting the difference existing woody vegetation, in order to support the discussion of urban forestry and environmental education as a mitigation measure the temperature increase and the favoring of thermal comfort. Data were collected in a well-wooded park, a plaza with trees isolated units and an area devoid of vegetation. The results showed that the urban trees influence the values of temperature and relative humidity, indicating a need for trees in urban areas, as a condition of thermal comfort. Is well established the role played by trees in reducing the heat generated in the urban environment, providing a favorable microclimate conditions with thermal comfort, reducing direct sunlight, expansion rates of evapotranspiration and reduced wind speeds, thus playing na important role in improving environmental conditions in cities and quality of life of its in habitants.